2003
DOI: 10.1002/macp.200350011
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Crystallization Kinetics of Melt Miscible Polyolefin Blends

Abstract: Blends of copolymers of ethylene/hexene (9 CH3/1 000 C) and ethylene/butene (77 CH3/1 000 C) synthesized with metallocene catalysts were prepared by co‐precipitation from solution. A phase diagram for this blend had been obtained in a preceding work, where the blends were found to be miscible in the melt with a characteristic upper critical solution temperature (UCST). In this work, the successive self‐nucleation and annealing (SSA) thermal fractionation method revealed that both pure copolymers, even though t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Generally, it is believed that lamellae thickness is related to the isotactic sequence distribution of polymer. There is a good correspondence between the SSA and the TREF techniques 39. The results of SSA are coincident with the results of high‐resolution 13 C‐NMR, TREF, and xylene solvent fractionation, but SSA can provide important quantitative information about the lamellar thickness distribution 29, 32.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Generally, it is believed that lamellae thickness is related to the isotactic sequence distribution of polymer. There is a good correspondence between the SSA and the TREF techniques 39. The results of SSA are coincident with the results of high‐resolution 13 C‐NMR, TREF, and xylene solvent fractionation, but SSA can provide important quantitative information about the lamellar thickness distribution 29, 32.…”
Section: Introductionsupporting
confidence: 63%
“…There is a good correspondence between the SSA and the TREF techniques. 39 The results of SSA are coincident with the results of high-resolution 13 C-NMR, TREF, and xylene solvent fractionation, but SSA can provide important quantitative information about the lamellar thickness distribution. 29,32 With the increase of separation temperature, the component separated by TREF shows higher melting temperature and longer crystalline sequence length after SSA treatment.…”
Section: Introductionsupporting
confidence: 52%
“…This technique is based on the sequential application of self-nucleation and annealing steps to a polymer sample originally devised by Fillon et al [32,44,45] and has been widely used to analyze the chain structures of semi-crystallized polymers such as PE and PP [46][47][48][49][50][51]. For a SSA fractionated polymer sample, the final DSC heating run will reveal a distribution of melting points induced by thermal treatment indicating the heterogeneous nature of the chain structures of the polymer.…”
Section: Thermal Fractionationmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Mu †ller and Arnal 23 summarized these results and they observed that, in thermal fractionation, the polymer chains are never physically separated, and therefore the technique is sensitive to linear and uninterrupted chain sequences. This implies that thermal fractionation is equally sensitive to both intra-and intermolecular defects.…”
Section: Introductionmentioning
confidence: 99%